Sustainability Accounting pada Perikanan Tangkap - Pelupessy, James (Jurnal Administrasi Terapan, 2026)
How is the performance of the Maluku fisheries sector reported not only through financial accounting but also through sustainability accounting, which measures and balances economic, social, and environmental dimensions in an integrated and auditable manner? This research employed a qualitative approach. Developing a simple, contextual, and sustainability-oriented economic recording and reporting model is an urgent need to strengthen the sustainability of capture fisheries in Maluku Province. Keywords: sustainability accounting, recording model